2009
DOI: 10.1038/leu.2009.259
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of the Japanese Childhood Cancer and Leukemia Study Group studies 811, 841, 874 and 911 on childhood acute lymphoblastic leukemia

Abstract: We analyzed the long-term outcomes of 1021 patients with acute lymphoblastic leukemia (ALL), enrolled in four successive clinical trials (ALL811, ALL841, ALL874 and ALL911) between 1981 and 1993. All patients received risk-adopted therapy according to leukocyte count and age at the time of diagnosis. The median follow-up durations of the four studies were 17.8 years in ALL811, 15.5 years in ALL841, 11.9 years in ALL874 and 15.8 years in ALL911. Patients' event-free survival (EFS) and overall survival (OS) rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 29 publications
(33 reference statements)
2
14
0
Order By: Relevance
“…Although the use of intensive chemotherapy has enabled patients with T-cell ALL to fare as well as patients with B-cell precursor ALL in some studies, the outcomes are significantly worse for the patients with T-cell ALL in most treatment protocols [3][4][5][6][7][8][9][10][11][12][13][14][15]. Chromosomal alterations, including numbers and translocations, have helped to classify pediatric patients with B-cell precursor ALL and improve treatment outcomes in the past three decades [16].…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of intensive chemotherapy has enabled patients with T-cell ALL to fare as well as patients with B-cell precursor ALL in some studies, the outcomes are significantly worse for the patients with T-cell ALL in most treatment protocols [3][4][5][6][7][8][9][10][11][12][13][14][15]. Chromosomal alterations, including numbers and translocations, have helped to classify pediatric patients with B-cell precursor ALL and improve treatment outcomes in the past three decades [16].…”
Section: Introductionmentioning
confidence: 99%
“…Rizzari and colleagues showed that trough asparaginase activity levels of < 0.05 IU/mL, obtained either with native E. Coli or Erwinia asparaginase, resulted in serum and CSF asparagine depletion in children with ALL. 25 In some studies activity levels as low as 0.02 IU/mL 26,27 or 0.03 IU/mL 21,28 resulted in sufficient depletion. In contrast, the only study indicating that higher activity levels are needed is a recent COG study of two pegylated E. coli asparaginase preparations, calaspargase pegol and pegaspargase, in which the plasma asparagine level began…”
Section: What Defines Optimal Asparaginase Activity?mentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][23][24][25][26] As typified by these randomized clinical trials where statistically significant differences in outcomes were found between treatment regimens, improvement has generally been observed with intensified therapy, but the impact of treatment intensification has been more apparent on EFS than survival.…”
Section: Introductionmentioning
confidence: 99%
“…1 Long-term survival has become the reality for the majority of children diagnosed with ALL, with approximately 85% surviving 5 years or longer after diagnosis. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] However, depending on certain risk factors, such as age at diagnosis, presenting white blood cell (WBC) count, hematopoietic lineage of the disease, and cytogenetic abnormalities, approximately 20% will experience relapse, 2-15 most of whom are destined to die of their disease. [16][17][18][19][20][21][22] Because of the relatively high prevalence of newly diagnosed ALL, relapsed ALL itself remains a common malignancy and a major cause of death among children.…”
Section: Introductionmentioning
confidence: 99%